Criminal Liability in Press Law and Artificial Intelligence-Generated Disinformation: Urgency of Reform in Indonesia - Arifin, Zainal; Handayani, Emi Puasa (Jurist-Diction, 2025)
Artificial intelligence (AI) presents significant challenges to the criminal liability framework under Indonesian press law, particularly in the regulation of AI-generated disinformation. This paper addresses these challenges through normative legal research, employing statutory, comparative, and conceptual approaches. The findings demonstrate that existing press law provisions are inadequate to regulate the complexity of AI-driven disinformation. This inadequacy has created a legal vacuum regarding accountability, undermining both legal certainty and the effectiveness of press regulation in the digital era. The paper argues that reform is urgently required to strengthen accountability while safeguarding press freedom. Such reform must incorporate the principles of prudence, independence, and AI ethics to ensure that press law remains responsive to technological innovation and continues to uphold the integrity of digital journalism.